Mortality of filling station attendants. - Lagorio, Susanna; Forastiere, Francesco; Iavarone, Ivano; Rapiti, E.; Vanacore, N.; Perucci, C. A.; Carere, A. (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--Gasoline contains established human carcinogens, such as benzene. The health impact of exposure to this fuel, however, has not been fully elucidated. We report on the mortality of a cohort of 2665 filling station managers from the Latium region (Italy). METHODS--This is the first workplace-based cohort of gas station attendants. However, only self-employed individuals were available for study (about 50% of the whole work force). The follow-up period extended from 1981 through 1992. The mortality experience of the cohort was compared with that of the regional population. RESULTS--The overall analysis for standardized mortality ratios (SMR) showed a significantly decreased mortality from all causes, mainly due to a deficit of cardiovascular diseases and malignant neoplasms. Nonsignificantly increased risks for esophageal cancer [SMR 241, 90% confidence interval (90% CI) 82-551], brain cancer (SMR 195, 90% CI 77-401) and non-Hodgkin's lymphoma (SMR 173, 90% CI 47-448) were found for the men; mortality due to lung cancer and leukemia was lower than expected, and no kidney cancer death was recorded. Among the attendants of small stations (characterized by a small number of employees and high sales of gasoline per full-time employee), the SMR values for esophageal cancer (for men SMR 351, 90% CI 120-803) and brain cancer (for men and women SMR 266, 90% CI 105-559) showed increased values. CONCLUSIONS--Filling station attendants are exposed to gasoline vapors and seem at risk of cancer of various sites. Due to the power limitations of this study, however, a precise estimate of the risk for many causes of death was not achievable. Further cohort studies of greater size are warranted.